(untitled) - Vogel, Ezra F. (Berkeley, 1975)
This book constitutes the first attempt of its kind to probe the major features of modern Japanese organization that have played such a critical role in Japan's extraordinarily rapid economic development. The contributors include prominent academic business consultants such as Peter Drucker of the United States and Kazuo Nada of Japan. Japanese government officials such as Yoshihisa Ojimi, former Administrative Vice-Minister of the Ministry of International Trade and Industry, and Taishiro Shiral, a member of the Central Labor Relations Commission: as well as outstanding Western experts on modern Japanese organization. The essays deal not only with Japanese government organization and business but also with the structures of a newspaper and a university and with the role of Japanese intellectuals in modern organization.
Keywords: Organization,Tổ chức; Industrial organization,Tổ chức công nghiệp